Highly Efficient and Stable Mn-Co1.29Ni1.71O4 Electrocatalysts for Alkaline Water Electrolysis: Atomic Doping Strategy for Enhanced OER and HER Performance - Yijia Cheng; Xingyan Guo; Zhizheng Ma; Kehan Dong; Lihua Miao; Shuai Du (Molecules, 2025)
Water electrolysis for hydrogen production has garnered significant attention due to its advantages of high efficiency, environmental friendliness, and abundant resources. Developing cost-effective, efficient, and stable materials for water electrolysis is therefore crucial. In this work, we synthesized a series of highly efficient multifunctional Mn-Co1.29Ni1.71O4 electrocatalysts through an atomic doping strategy for alkaline electrocatalysts. The unique structure features and large specific surface area of these catalysts provide abundant active sites. The Mn-Co1.29Ni1.71O4 catalysts exhibit an excellent oxygen evolution reaction (OER) performance in 1.0 M KOH electrolyte, with an overpotential of 334.3 mV at a current density of 10 mA cm−2 and 373.3 mV at 30 mA cm−2. Additionally, the catalysts also demonstrate a Tafel slope of 76.7 mV dec−1 and outstanding durability. As hydrogen evolution reaction (HER) electrocatalysts, it shows an overpotential of 203.5 mV at −10 mA cm−2 and a Tafel slope of 113.6 mV dec−1. When the catalysts can be utilized for the overall water splitting, the catalyst requires a decomposition voltage of 1.96 V at 50 mA cm−2. These results indicate that the high catalytic activity and stability of Mn-Co1.29Ni1.71O4 samples make it a highly promising candidate for industrial-scale applications.